Pulse Polarographic Studies on Metal ion Interaction with DNA - Kozlowski, Henryk; Pawlowski, Tomasz; Swiatek, Jolanta (Asian Journal of Chemistry, 2010)
The application of the differential pulse-polarography and sweep voltammetry to the studies of the metal ion interaction with DNA have shown that the local labilization of the double stranded structure of nucleic acid caused by e.g. charged surfaces may be of critical importance for such interaction. The opening of the double helix stimulates the metal ion binding to nucleic bases. This interaction is of minor importance when the intact DNA structure is available for metal ions. The polarographic techniques are very useful in the study of the local defects of the structure of the DNA molecule and of their influence on the metal ion binding. Such situation may happen on the biological membrane which is electrically charged and whose electric charge may be imitated by the mercury electrode surface.